Computational and experimental approaches in understanding the therapeutic potential of Ficus deltoidea Jack leaf extract / Amirul Ridzuan Abu Bakar - Amirul Ridzuan, Abu Bakar (2018)
Ficus deltoidea Jack of family Moraceae (FD) is a native shrub in Malaysia that are well known for its ethno-pharmaceutical and therapeutic properties. In this study, computational and experimental approaches were adopted to unravel the therapeutic properties of the FD leaf. Initially, quality control and safety assessment on the FD leaf were undertaken. The findings from this analysis revealed that the FD leaf of high quality, purity and abide by the safety requirements set by the regulatory body. FD leaf was solvent extracted as 50% (v/v) ethanol water extract. Standardization using high performance liquid chromatography (HPLC) revealed vitexin and isovitexin as the major chemical compounds in the FD leaf 50% (v/v) ethanol water extract. FD leaf 50% (v/v) ethanol water extract and its major chemical compounds (vitexin and isovitexin) were subjected to a selected panel of enzymatic inhibition assay, namely, α-amylase and matrix metalloproteinases (MMP-2, MMP-8 and MMP-9). The results showed that FD leaf 50% (v/v) ethanol water extract, vitexin and isovitexin exhibited inhibition property against the selected enzyme panels. Then, computational analyses (molecular docking and molecular dynamic simulation) revealed the molecular interaction and ligand-protein complex stability between vitexin and isovitexin against the selected enzyme panels. FD leaf 50% (v/v) ethanol water extract also showed antioxidant activity based on the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and in vitro cytotoxicity based on 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay revealed the IC50 of the extract was at 221 μg/ml on EA.hy926 cells. FD leaf 50% (v/v) ethanol water extract also demonstrated cell migration inhibitory effect on EA.hy926 cells in a dose and time-dependent manner with the highest activity tested at 300 μg/ml after 24 hours treatment. The biological activity of FD leaf 50% (v/v) ethanol water extract was further studied using 2 types of in vivo animal models (healthy and streptozotocin-induced diabetic Sprague-Dawley rats). Toxicology analysis was conducted at 1000 mg/kg of FD leaf 50% (v/v) ethanol water extract. Visual inspection, blood analysis and histology analysis revealed no acute toxicity of the leaf extract at the tested concentration. Wound healing activity of FD leaf 50% (v/v) ethanol water extract was studied on both animal models. FD leaf 50% (v/v) ethanol water extract showed highest wound healing property at 100 mg/ml and the diabetic rat model showed faster wound closure rate compared to the healthy rat model. Finally, this study provided comprehensive and valuable information on the potential of FD leaf extract for therapeutic application especially for the wound healing in diabetic cases.